a , b , c are real numbers in the following equation system:
⎩ ⎪ ⎨ ⎪ ⎧ a b ( a + b + c ) = 1 0 0 1 b c ( a + b + c ) = 2 0 0 2 c a ( a + b + c ) = 3 0 0 3
Find a b c
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
1 0 0 1 / a b = 2 0 0 2 / b c = 3 0 0 3 / c a 1 / a b = 2 / b c = 3 / c a 2 a = c = 3 b 2 a 2 ( a + 2 a + 2 / 3 a ) = 3 0 0 3 2 2 a 3 = 9 0 0 9 a b c = a ∗ 2 a ∗ ( 2 / 3 ) a = ( 4 / 3 ) a 3 = ( 9 0 0 9 / 2 2 ) ∗ ( 4 / 3 ) = 3 0 0 3 ∗ 2 / 1 1 = 6 0 0 6 / 1 1 = 5 4 6
Exactly the same way.
lets take ratios, very simply, we can get that a b : b c : c a = 1 : 2 : 3 now separate the ratios a b : b c = 1 : 2 ⟶ a : c = 1 : 2 c a : b c = 3 : 2 ⟶ a : b = 3 : 2 add these ratios to get a : b : c = 3 : 2 : 6 and hence, a = 2 3 b , c = 3 b , b = b so, a b c = 2 9 b 3 now solve any 1 equation, b c ( a + b + c ) = 2 0 0 2 ⟶ 3 b 2 × 2 1 1 b = 2 0 0 2 and solve b 3 = 3 3 6 4 now insert it, a b c = 2 9 b 3 = 2 9 × 3 3 6 4 = 5 4 6
Dividing the first equation by the second and the first by the third, we obtain
a = 2 1 c and b = 3 1 c
Substituting these values into the first equation, we obtain
1 0 0 1 = a b ( a + b + c )
= a b ( 2 1 c + 3 1 c + c )
= 6 1 1 a b c
Hence, a b c = 5 4 6
Problem Loading...
Note Loading...
Set Loading...
Multiply the three equations:
a 2 b 2 c 2 ( a + b + c ) 3 = 1 0 0 1 ⋅ 2 0 0 2 ⋅ 3 0 0 3
Now, multiply the three equations, two at time:
a b 2 c ( a + b + c ) 2 = 1 0 0 1 ⋅ 2 0 0 2 a 2 b c ( a + b + c ) 2 = 1 0 0 1 ⋅ 3 0 0 3 a b c 2 ( a + b + c ) 2 = 2 0 0 2 ⋅ 3 0 0 3
Sum those three equations:
a b c ( a + b + c ) 3 = 1 0 0 1 ⋅ 2 0 0 2 + 1 0 0 1 ⋅ 3 0 0 3 + 2 0 0 2 ⋅ 3 0 0 3
Finally, divide the first equation we obtained by this one:
a b c = 1 0 0 1 ⋅ 2 0 0 2 + 1 0 0 1 ⋅ 3 0 0 3 + 2 0 0 2 ⋅ 3 0 0 3 1 0 0 1 ⋅ 2 0 0 2 ⋅ 3 0 0 3 a b c = 5 4 6